The Indication of Gastropods Extinctions at Intertidal Zone of the Teluk Nipah Waters, the Pesisir Selatan Regency the Province of the West Sumatera - Afrizal Tanjung (Jurnal Natur Indonesia, 2023)
Intensive observation of gastropods, every March from the year 2008 to the year 2012, was carried out to document some indicators of gastropod extinction. The purposive sampling technic was used in this work. The physicochemical parameters of its habitat were also monitored during every sampling done.  It was found that the intertidal substrate consist of sand, while the habitat parameters were more than 5,6 mg/L dissolved oxygen, pH around 7,0-7,2, salinity 30,2-32,2 ppt, temperature 28,6-29,60C, the visibility 100%.  The number of species, the number of found gastropods, the abundance, and the maximum shell size of found gastropods showed decreasing from year to year, while routine collecting by the visitor and the marine organism shell collector, and the disturbance by the fisherman activities occurred. This indication showed a tendency for gastropods extinction